Hubungan Antara Self-efficacy dan Dukungan Sosial dengan Psychological Distress pada Perawat di Rumah Sakit “X” Bandung - Maria Yuni Megarini; Trisa Genia; Yuspendi Yuspendi (Universitas Kristen Maranatha, 2022)
Nurses during the Corona Virus Disease-19 (Covid-19) pandemic are expected to be able to provide professional nursing services even with the risk of contracting and even becoming victims of Covid-19. Working in a hospital with current pandemic conditions causes nurses to experience psychological disorders such as depression, anxiety and stress. The purpose of this study was to determine the relationship between self-efficacy and social support with psychological distress in nurses at